The role of ICT on agricultural knowledge management in Ethiopia: a case study on Woreda knowledge centers in Bure, Goma, Alaba and Alamata - Lemma, F. (Unity University, 2009)
This Study analysed the perspective that information technology can play a central role in knowledge management processes and its challenges and opportunities in the context of Ethiopian infrastructure in the cases under study. It was undertaken in four regions of Ethiopia taking one Woreda Knowledge Centre (WKC) from each region based on purposive sampling method. The study was aimed to assess the role of ICT in IPMSs’ projects of ICT-based Woreda Knowledge Centers (WKC) to investigate if such centers can exploit the opportunity of the ICT-based WKCs for the purpose of enhancing effectiveness of the users. The respondents are the staffs of WOoARD who are using the knowledge centers. Both qualitative and quantitative data were used to obtain reliable information from primary and secondary sources. Data is analysed more qualitatively and also done using descriptive statistics, Percentage and Ranking. The study indicated that the role of ICT in the WKCS is moderate. Due to lack of computer basic skills, shortage of ICT tools and others, there are many challenges that have to be given solutions. The study recommended the way these challenges can be solved. The study also revealed that, the inefficiency of Ethiopian Telecommunication is becoming the obstacle for the process of Knowledge Management (KM) by hindering that there is very poor network connection in all regions so that it is difficult to get and/or disseminate the agricultural information and knowledge by the agricultural service providers.